4510=36l

Rewrite the equation as 36l=4510.

36l=4510

Factor 5 out of 45.

36l=5(9)10

Cancel the common factors.

Factor 5 out of 10.

36l=5⋅95⋅2

Cancel the common factor.

36l=5⋅95⋅2

Rewrite the expression.

36l=92

36l=92

36l=92

Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.

36⋅2=l⋅9

Rewrite the equation as l⋅9=36⋅2.

l⋅9=36⋅2

Multiply 36 by 2.

l⋅9=72

Divide each term by 9 and simplify.

Divide each term in l⋅9=72 by 9.

l⋅99=729

Cancel the common factor of 9.

Cancel the common factor.

l⋅99=729

Divide l by 1.

l=729

l=729

Divide 72 by 9.

l=8

l=8

l=8

Solve for l 45/10=36/l